Pemberian Tepung Daun Kelor (Moringa oleifera L) Melalui Pakan Sebagai PencegahanTerhadap Infeksi Bakteri Edwarsiella Ictaluri Pada Ikan Patin (Pangasius hypopthalmus) - Yuda Saputra; Syahrizal Syahrizal; Safratilofa Safratilofa; Edy Barkat Kholidin (Jurnal Akuakultur Sungai dan Danau, 2020)
The purpose of this study was to determine the effect of giving Moringa oliefera L leaf meal through feed as an anti-bacterial to prevent infection with E.ictaluri bacteria in catfish (Pangasius hypopthalmus). This research was conducted from March 2020 to April 2020 at the Fish Health Laboratory, Freshwater Aquaculture Fisheries Center (BPBAT) Jambi. The research method used was a completely randomized design with five treatments and three replications. Catfish were fed for 14 days with treatment feed with each treatment (A. 5% / kg feed), (B. 10% / kg feed), (C. 15% / kg feed), (D. Commercial feed ) and (E. Commercial feed). and on the 16th day the fish were injected with the Edwarsiella ictaluri bacteria, and survival was observed from day 16 to day 26. The results showed that treatment of moringa leaf meal (C. 15% / kg of feed), could prevent bacterial infection E. ictaluri in catfish with the highest survival rate reaching 66.67%, fish growth of 5.78 grams / head, and feed conversion of 0.18% / kg of feed.